ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS STORYLINE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS IV SD CERDAS BANGSA - Aulia Putri Amhar; Arrini Sabrina Ansho; Sukmawati; Sujarwo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to identify the obstacles faced in implementing Storyline-based learning media in the classroom and to determine the perceptions of students and teachers towards the use of Storyline-based learning media. In this study, a qualitative approach will be applied through a case study method. The research sample was 23 people. This study was conducted in the fourth grade of the Ra Kartini Cerdas Bangsa Private Elementary School on Jl. Jati Rejo, Medan Estate, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra 20371. The use of Storyline-based learning media has been shown to increase student engagement and focus in reading. Visualizing stories through images makes it easier for students to understand the learning context, increases attention, and reduces boredom during learning activities. Students' reading skills showed positive developments during the implementation of Storyline-based learning media. Students were increasingly able to identify the storyline, read short sentences with more confidence, and understand the relationship between images and text. Shared reading activities and story sequencing played a role in strengthening students' understanding of the reading content. Student participation in learning increased throughout the learning process. Adjustments made by teachers, such as simplifying the storyline, improving the quality of visuals, and adjusting the pace of material delivery, encouraged students to be more active in answering questions, discussing, and taking turns reading. Teachers find it easier to deliver reading material. Storyline media helps teachers deliver material in a structured and engaging manner. Teachers also feel that the use of visuals can clarify learning messages and make it easier for students to understand the story's content. Questionnaire and interview data show a positive response from teachers and students to the use of Storyline media. Students feel that learning becomes more interesting and easier to understand, while teachers assess the media as relevant to student characteristics and appropriate to classroom learning needs. Overall, Storyline-based learning media can be an effective alternative in improving reading skills and creating more interactive, enjoyable, and meaningful learning for fourth-grade students.